REVITALISASI KAWASAN PECINAN SURYAKENCANA BOGOR SEBAGAI SEBUAH STRATEGI DALAM MENINGKATKAN CITRA KAWASAN - Ryan Salim; Nina Carina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Suryakencana Street in the Suryakencana Chinatown Area, Bogor City is famous for its culinary delights. Although currently the culinary diversity in Suryakencana continues to grow, the presence of other culinary spots in Bogor has made Suryakencana's culinary name start to fade. To be able to restore and strengthen the image of the Suryakencana Area as a tourist visit route, new attractors are needed. The existence of the new attractor can improve the image of the Chinatown area, elevate Chinatown culture and make the Suryakencana area a culinary tourism area and Chinatown culture. The urban acupuncture method is used in selecting points that need to be "healed" as well as selecting new functions as attractors with the aim of improving the image of the faded Chinatown area. The selection of cultural functions as attractors is realized in a cultural center that is not only a place for cultural performances, but also can accommodate the needs of the local community for the need for shared space, expression space, and commercial space. Suryakencana Cultural Center can be a new magnet for this area. This cultural center will also be a link between the northern area of ​​the area where there are temples and markets, with the southern area which is the culinary area. The presence of this cultural center makes the culture in the Suryakencana Chinatown area to survive in line with the development of the city of Bogor. Keywords: Acupuncture; Attractor; Chinatown; Culture; Suryakencana Abstrak Jalan Suryakencana di Kawasan Pecinan Suryakencana, Kota Bogor terkenal akan kulinernya. Walaupun saat ini keragaman kuliner di Suryakencana terus bertambah namun kehadiran titik kuliner lain di Bogor menjadikan nama besar kuliner Suryakencana mulai pudar. Untuk dapat mengembalikan dan memperkuat citra Kawasan Suryakencana sebagai jalur kunjungan wisata, diperlukan attractor baru. Keberadaan attractor baru tersebut dapat meningkatkan citra kawasan pecinan, mengangkat budaya pecinan dan menjadikan kawasan Suryakencana sebagai kawasan wisata kuliner dan budaya pecinan. Metode  urban acupuncture digunakan dalam memilih titik yang perlu di “sembuhkan” serta pemilihan fungsi baru sebagai attractor dengan tujuan meningkatkan citra kawasan pecinan yang sudah pudar. Pemilihan fungsi budaya sebagai attractor diwujudkan dalam sebuah cultural centre yang tidak hanya menjadi tempat pertunjukan budaya, tetapi juga bisa mengakomodir kebutuhan masyarakat setempat akan kebutuhan ruang bersama, ruang ekspresi, serta ruang komersil. Suryakencana Cultural Center dapat menjadi magnet baru bagi kawasan ini. Cultural centre ini juga akan menjadi penghubung antara area utara kawasan yang mana terdapat vihara dan pasar, dengan area selatan yang merupakan area kuliner. Kehadiran Cultural Centre ini membuat budaya pada Kawasan Pecinan Suryakencana dapat bertahan sejalan dengan berkembangnya Kota Bogor.